2022
DOI: 10.21203/rs.3.rs-2248784/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Irisin ameliorates myocardial ischemia-reperfusion injury through modulation of gut microbiota and intestinal permeability in rats

Abstract: Purpose Irisin has a significant protection the myocardial from ischemia reperfusion (I/R) injury. Recent studies have suggested that the gut microbiota plays an important role in the progression of myocardial I/R injury. In this context, the aim of this study is to investigate whether Irisin interferes in gut microbiota and gut mucosal barrier during myocardial I/R injury. Methods All the rats received intraperitoneal injection of irisin or PBS, and then myocardial I/R rats disease model was established. Gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…51 Interestingly, it has been reported that irisin administration can counterbalance gut dysbiosis and improve the integrity of the gut mucosal barrier induced in rats that underwent an experimental model of myocardial ischemia–reperfusion injury with MIF. 52…”
Section: Potential Of Addressing Gut Alterations To Reduce Mif and Hf...mentioning
confidence: 99%
“…51 Interestingly, it has been reported that irisin administration can counterbalance gut dysbiosis and improve the integrity of the gut mucosal barrier induced in rats that underwent an experimental model of myocardial ischemia–reperfusion injury with MIF. 52…”
Section: Potential Of Addressing Gut Alterations To Reduce Mif and Hf...mentioning
confidence: 99%